Two prospective doubled haploid rice lines VH1 and VH2 obtained by anther culture - Van, Nghiem Nhu; Binh, Le Tran; Muoi, Le Thi (Academia Journal of Biology, 2015)
Two prospective doubled haploid rice lines VH1 and VH2 obtained by anther culture